(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the methodology of teaching the native language in primary grades, focusing on contemporary approaches, strategies, and challenges. In the context of modern education, native language instruction plays a pivotal role in laying the foundation for a child’s cognitive and emotional development. The paper discusses the various methods employed in primary schools to enhance language acquisition, including traditional approaches as well as modern techniques. Special attention is given to the integration of technology, the role of cultural context in language learning, and the importance of fostering a deep connection with one’s cultural and linguistic heritage. The article also addresses the challenges faced by teachers in diverse classrooms, where varying levels of language proficiency and external influences can affect the learning process. Through examining current research and methodologies, this paper aims to highlight effective teaching strategies that cater to the evolving needs of young learners and promote the development of literacy skills in the native language.